2019
DOI: 10.1016/j.heliyon.2019.e02974
|View full text |Cite
|
Sign up to set email alerts
|

Extension of planned behavioral theory to consumer behaviors in green hotel

Abstract: This study aims to contribute to the development of an extended theory of planned behavior to understand the indicators of consumer behavior. A conceptual framework highlighting four study constructs (i.e., personal norms, intention towards green hotels, environmental consciousness, and green consumer behavior) was tested using 394 general Malaysian lodging consumers. The findings indicate that to devise green branding strategies for the hotels, the managers must first consider how the environmental consciousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 39 publications
4
63
0
Order By: Relevance
“…The empirical result of PLS-SEM indicates that environmental concern (EC) has a strong influence on young, educated consumers' green purchasing decisions in Bangladesh, and therefore, Hypothesis (H1) is supported. These findings support those obtained in the previous foreign survey in developed countries [2,17,20,23,24,28,29,71,72,74]. They also prove that environmental concern (EC) has a positive impact on ecological purchasing decisions on green foods [72,112].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The empirical result of PLS-SEM indicates that environmental concern (EC) has a strong influence on young, educated consumers' green purchasing decisions in Bangladesh, and therefore, Hypothesis (H1) is supported. These findings support those obtained in the previous foreign survey in developed countries [2,17,20,23,24,28,29,71,72,74]. They also prove that environmental concern (EC) has a positive impact on ecological purchasing decisions on green foods [72,112].…”
Section: Discussionsupporting
confidence: 89%
“…Customers who are worried about environmental issues are positive about green products and highly motivated to buy eco-friendly products to maintain a good healthy lifestyle [68][69][70]. Earlier scholars found in their study that environmental concern affects the consumer's purchasing decision process, especially for green products [17,23,61,71,72]. At present, young, educated consumers are anxious about the environment.…”
Section: Environmental Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the novel green consumption trend among community encourages every member to understand and alter their conventional consumption patterns in their purchase intentions in pursuing environmental sustainability (Ahmad at al., 2020;Brutting et al, 2020;De Aquim et al, 2019;Prakash et al, 2019;Jaiswal and Kant, 2018;Nie et al, 2018). Research on green products' consumer purchase intentions has been widely conducted (Chairy, 2012;Joshi and Zillur, 2015;Mobrezi and Khoshtinat, 2016;Bashir et al, 2019;Agmeka et al, 2019). Kim and Hwang (2020), in their study, explain that the intention of environmentally friendly behavior related to the theoretical framework and product knowledge about the pro-environment in terms of goods (food) delivery services using drones to reduce air pollution from goods delivery vehicles (food).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Bashir et al (2019) found that behavioral intention towards the environment mediates the relationship between consumers' norms and green consumer behavior. Furthermore, Ng and Law (2015) argued that people with an internal locus of control (LOC) show a positive attitude towards environmentally friendly products.…”
Section: Introductionmentioning
confidence: 99%